Carbon Disclosures: Comparability, the Carbon Disclosure Project and the Greenhouse Gas Protocol - Jane Andrew; Corinne L. Cortese (Australasian Accounting, Business and Finance Journal, 2012)
Corporate carbon disclosures have become increasingly commonplace and are often presented as a useful voluntary mechanism for internal and external decision making. The production of the data is said to assist corporations position themselves strategically in terms of the carbon risks and opportunities they may face. External to the firm, carbon disclosures hold the promise of assisting capital allocation decisions that are ‘carbon responsible’. It is claimed that the process of disclosure can sensitise the market to global environmental problems such as climate change. In order to consider these claims, the broad purpose of this paper is to question whether the voluntary information that is produced can live up to its expectations and provide a meaningful basis for climate change related decision making. To that end, this exploratory study examines the carbon disclosures of Australasian mining companies over three years in compliance with a voluntary carbon disclosure regime – the Carbon Disclosure Project (CDP) – and assesses those disclosures with respect to comparability, an important criterion for information usefulness.
Keywords: Carbon regulation; climate change; carbon accounting; carbon disclosures